TECHNOLOGICAL CLUB CONVERGENCE IN THE CONTEXT OF GLOBAL TENDENCIES OF INNOVATIVE DEVELOPMENT - E. Smirnov (Publishing House of the State University of Management, 2016)
In the article groups of the countries concerning their technological proximity are considered that reflects processes of club convergence. As individual technologies become public, they radically change process of functioning of the national economies. On the example of development of some regional integration associations the interrelation of technological, innovative convergence and the main directions of economic development is established.